Granting of Legal Experts as a Invention of Law Model Through Legal Research on The Criminal Justice System - Erdianto Effendi (Unram Law Review, 2019)
com Invention of law activity by judge is not optimum because the judge must be rolled from a region to other region. While the judge is hoped to find the living law. This article concluded that invention law by judge should be aided by granting of legal expert in Th Criminal Justice System. Legal researcher should hoped to invent the living law in comunity. unity.